Alterações químicas no solo e na água de drenagem decorrentes da aplicação da água residuária do processamento dos frutos do cafeeiro - Cabanêz, Paula Alvarez (2010)
Reuse of crop residues in agriculture is a promising alternative, which allows sustain agroenvironment providing improvements to the soil-plant system. This sense, the wastewater coming from the processing of coffee fruits (ARC) can be used as natural fer